THE HUMAN BODY AND BLACK PEOPLE IN BIOLOGY TEXTBOOKS (Revista Contexto & Educação, 2019)
The racial relations in Nature Sciences are little studied. However its a área that can contribute for combat racism. We need understand how the biology teachig is influencied for historical constructs about racial relations. This is fundamental so that we can combat hierarchizations, stereotypes and negative representations for black people in Science teaching. The knowledge about history of Science, scientific racism and social representation, help us to interpret this phenomenon better. In this research we analyze biology textbooks and how human bodys was represent. We find few representations of black people in this material. The human body was represent, in the most times, for white body. This seems to be the universal human.